Hermann Hesse's Hegelianism: The Progress of Consciousness Towards Freedom in The Glass Bead Game - John Krapp (Studies in 20th & 21st Century Literature, 2002)
Hermann Hesse's novels commonly represent characters' struggles through ideological opposition and conflict towards resolution. The majority of his critics attribute Hesse's interest in, and expression of, this struggle to his lifelong study of Eastern philosophy. However, Hesse's interest in things Eastern need not be taken as the exclusive determinant of the theme of individuation represented in his fiction. This essay argues that Hesse's predilection for elaborating the ideological crises and resolutions of his characters may also be interpreted as reflecting the Western, Hegelian concept of an Absolute Spirit that proceeds through exhaustive dialectical permutations before it becomes conscious of its status as the identical subject-object of history. The essay begins with an account of critical commentary on Hesse's knowledge and estimation of Hegel. Thereafter, the theoretical affinities between Hesse and Hegel are investigated. The essay concludes with a close analysis of Hegelian imprints in Hesse's final and most complex novel, The Glass Bead Game.
Keywords: Hermann Hesse; Eastern philosophy; Western; Hegelian; Absolute Spirit; conscious; history; subject-object of history; Hegel; The Glass Bead Game; German; Das Glasperlenspiel